1936
DOI: 10.1128/jb.32.1.89-103.1936
|View full text |Cite
|
Sign up to set email alerts
|

The Life Cycle of the Organism Causing Yeast Meningitis

Abstract: In studying the characteristics of several strains of the organism commonly called Torulk histolytica, some rather prominent structures were noted, the significance of which seems to have been overlooked in previous descriptions. The study of the nature of these bodies disclosed a sequence of changes in morphology which necessitates a revision of the classification of at least some of the members of this group. One of the strains studied was isolated on four occasions from the spinal fluid of a patient in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1941
1941
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…On the basis of preliminary observations, Wickerham (1944) concluded that it was unlikely that the yeast belonged in any of the present genera of sporogenous yeasts since none of the latter contain yeasts with its characteristics, such as mucoid cell material, colored ascospores, ascospores in excess of eight when cultured on certain media, and a strong tendency of old cells to shed their outer membranes. In some respects the yeast resembles a culture described as Debaryomyces hominis by Todd and Herrmann (1936). However, the structures which were described as spores of D. hominis are different from the spores of the soil yeast, but comparative studies might show more similarity between the two than is apparent from the description of Todd and Herrmann.…”
Section: Fig 8 Same As Figurementioning
confidence: 94%
“…On the basis of preliminary observations, Wickerham (1944) concluded that it was unlikely that the yeast belonged in any of the present genera of sporogenous yeasts since none of the latter contain yeasts with its characteristics, such as mucoid cell material, colored ascospores, ascospores in excess of eight when cultured on certain media, and a strong tendency of old cells to shed their outer membranes. In some respects the yeast resembles a culture described as Debaryomyces hominis by Todd and Herrmann (1936). However, the structures which were described as spores of D. hominis are different from the spores of the soil yeast, but comparative studies might show more similarity between the two than is apparent from the description of Todd and Herrmann.…”
Section: Fig 8 Same As Figurementioning
confidence: 94%
“…Since spore-formation is often delayed, cultures should be examined repeatedly over a period of several weeks before they are to be labelled as asporogenous. Windisch (1938) reported spore formation in Torulopsis pulcherrima only after the agar cultures had dried considerably, and Todd and Herrmann (1936) had the same experience with Debaryomyces neoformans. Fuchs (1935) found that with old laboratory strains which had quit forming spores this character could be revived by growing them on wort agar, transferring the young growth to plaster blocks, then back to wort agar, and so on.…”
Section: Technical Procedures For the Identification Of Yeastsmentioning
confidence: 91%
“…Diddens and Lodder (1939b) record the discovery of spores in the following yeasts formerly reported as asporogenous, with the changes in nomenclature in-dicated: Monilia pinoyisimilis and Monilia pseudotropicalis = Saccharomyces fragilis; Monilia macedoniensis = Saccharomyces macedoniensis; Monilia javanica = Hansenula anomala; Candida pelliculosa = Hansenula javanica. Todd and Herrmann (1936), confirmed by Giordano (1939), noted that many strains of pathogenic yeasts formerly referred to as Torula histolytica, Torula hominis, etc. actually form spores of such a character as to warrant referring them to the genus Debaryomyces.…”
Section: Teee Yeastsmentioning
confidence: 92%
See 1 more Smart Citation